Facilitating early diagnosis of chronic thromboembolic pulmonary hypertension with dynamic chest radiography: Protocol for a multicenter, assessor-blinded, case-wise randomized superiority reader study (FIND-DCR) - Kazuya Hosokawa; Yuzo Yamasaki; Junji Kishimoto; Tomomi Nagayama; Shiro Adachi; Shinji Naganawa; Takumi Inami; Kenichi Yokoyama; Satoshi Yasuda; Kei Takase; Kayoko Kubota; Takashi Yoshiura; et al. (PLoS ONE, 2026)
Introduction Chronic thromboembolic pulmonary hypertension (CTEPH) is a treatable cause of pulmonary hypertension but remains under-recognized and is often diagnosed with delay. Limited access to lung ventilation-perfusion (V/Q) scintigraphy, especially outside tertiary centers, is one contributor. Dynamic chest radiography (DCR), with a pulmonary circulation analysis program, can provide a rapid, non-invasive, and widely deployable assessment of pulmonary perfusion. We describe the protocol of a multicenter reader study testing whether adding DCR-based analysis to standard initial work-up improves diagnostic accuracy for CTEPH among patients with echocardiographically suspected pulmonary hypertension. Methods and analysis This investigator-initiated, multicenter, assessor-blinded, case-wise randomized superiority reader study compares standard initial work-up (blood tests, chest X-ray, ECG, pulmonary function tests, and transthoracic echocardiography per guidelines) with standard work-up plus DCR-based pulmonary circulation analysis. The primary endpoint is diagnostic accuracy for discrimination between CTEPH and non-CTEPH in the intention-to-treat set. The final diagnosis of CTEPH versus non-CTEPH will be defined as the reference standard according to the Japanese and European guidelines for pulmonary hypertension. Secondary endpoints include sensitivity, specificity, positive and negative predictive values; agreement with V/Q scintigraphy regarding regional perfusion defects using κ statistics; and STARD-conformant academic performance evaluation of DCR-based pulmonary circulation analysis and lung perfusion scintigraphy in relation to the site-level final diagnosis of CTEPH versus non-CTEPH in a full analysis set. Safety endpoints include adverse events during DCR acquisition and device malfunctions. The target sample size is 108 cases with 1:1 allocation. Recruitment started on 30/07/2025 and is expected to continue until 28/02/2027, with overall study completion planned for 31/05/2027. Discussion This multicenter reader study addresses a key limitation of current CTEPH diagnostic pathways—reliance on V/Q scintigraphy, which may be delayed or unavailable outside tertiary centers—by evaluating whether DCR-based pulmonary circulation analysis can improve early discrimination of CTEPH and support timely referral. Trial registration number Japan Registry of Clinical Trials (jRCT), jRCT2072250027.